2017
DOI: 10.1039/c6dt04088h
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine–imine and –enamido ligands for acceptorless dehydrogenation catalysis

Abstract: A highly tunable phosphine-imine ligand family is introduced. Following metallation with ruthenium, deprotonation of the ligand affords a phosphine-enamido species. Complexes with the ligand in both the imine and enamido forms are active toward acceptorless dehydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We hypothesized that a structurally responsive 1-azaallyl ligand could engender unusual and unexpected reactivity. To this end, we designed phosphine imine ligand 1 H (Scheme , left), a proligand to a phosphine 1-azaallyl ligand ( 1 ), by deprotonation at C 2 . Previously, we showed that an octahedral ruthenium complex with 1 exhibited only a κ 2 -P,N coordination mode.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that a structurally responsive 1-azaallyl ligand could engender unusual and unexpected reactivity. To this end, we designed phosphine imine ligand 1 H (Scheme , left), a proligand to a phosphine 1-azaallyl ligand ( 1 ), by deprotonation at C 2 . Previously, we showed that an octahedral ruthenium complex with 1 exhibited only a κ 2 -P,N coordination mode.…”
mentioning
confidence: 99%
“…The proligand 1 H reacts rapidly at room temperature with PdCl­(Me)­(COD) to give 2 , the structure of which was confirmed by single-crystal X-ray crystallography (Scheme ). The complex has a slightly distorted square planar geometry, as evidenced by a τ 4 value of 0.10 (for a perfect square plane, τ 4 = 0).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40–75 ppm (Table S1†). 36,47 Rather, the chemical shift is only ca. 3 ppm downfield from the analogous signal in 1 that has a μ-N binding mode of the 1-azaallyl fragment.…”
Section: Resultsmentioning
confidence: 99%
“…23 We have previously reported the synthesis and coordination chemistry of a ligand [Ph 2 P(C 6 H 4 )NCHC(CH 3 ) 2 ] − (L1) bearing phosphine and 1-azaallyl donor groups. [24][25][26] This ligand exhibits a broad range of coordination modes that depend on the metal, metal oxidation state, and the presence of additional L-donor ligands. In the presence of pyridine, a κ 2 -P,N mode was enforced to give coordinatively saturated Ru(II) or Pd(II) complexes (F and G, respectively).…”
Section: Introductionmentioning
confidence: 99%